2003
DOI: 10.1152/japplphysiol.00302.2003
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxemia and hepatic injury in a rodent model of hindlimb unloading

Abstract: Hindlimb unloading (HU) is known to induce physiological alterations in various organ systems that mimic some responses observed after exposure to microgravity. In the present study, the effects of up to 4 wk of HU on the liver were assessed in male Wistar rats and two mouse strains: endotoxin-sensitive C57BL/6 mice and endotoxin-resistant C3H/HEJ mice. Plasma levels of endotoxin, a known stimulator of hepatic injury, were measured in portal and systemic blood samples. Endotoxin was elevated by approximately 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 47 publications
4
34
1
1
Order By: Relevance
“…Our previous work and the present study (Fig. 3) demonstrated that lipid droplets accumulated in the cytoplasm of hepatocytes (38). Vecchini et al (46) investigated mechanisms underlying hepatic steatosis resulting from HU and found that mRNA levels and activities of several proteins that modulate hepatic lipid content were altered in favor of lipid accumulation.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Our previous work and the present study (Fig. 3) demonstrated that lipid droplets accumulated in the cytoplasm of hepatocytes (38). Vecchini et al (46) investigated mechanisms underlying hepatic steatosis resulting from HU and found that mRNA levels and activities of several proteins that modulate hepatic lipid content were altered in favor of lipid accumulation.…”
Section: Discussionsupporting
confidence: 65%
“…However, under pathophysiological conditions, intestinal permeability can increase significantly, allowing bacteria and bacterial components to leak into the circulation. In a previous study, we demonstrated that lowgrade portal endotoxemia was associated with hepatic injury in rats and C57BL/6 mice after HU (38). In contrast, no histological changes or significant increases in serum ALT activity were detected after HU in endotoxin-resistant C3H/HEJ mice despite portal endotoxin levels of 222 Ϯ 83.4 pg/ml.…”
Section: Mechanism Of Injury Involves Endotoxemia and Lipid Peroxidatmentioning
confidence: 84%
See 1 more Smart Citation
“…Evidently, the intestinal epithelium acts as a continuous barrier to avoid LPS translocation, but some endogenous or exogenous factors may alter this function. Among the factors promoting a leaky gut and increasing plasma LPS levels, alcohol consumption (29 -33), immobilization stress (33,34), and radiation (35) have been put forward. Most importantly, in most of these studies, antibiotic treatments were also administered and resulted in reduced plasma and cecal LPS levels.…”
Section: Discussionmentioning
confidence: 99%
“…Under simulated weightlessness, intestinal congestion and mucosa swelling were caused by dysfunction of mesentery minicirculation [16] , intestinal motivation was slowed down, colonic transit time was prolonged [17] and intestinal flora was altered [2] . All these abnormal changes may further cause inflammatory cytokines activation (such as IFN-r and TNF-α) [18] . It was reported the expression of TJ proteins could be regulated by IFN-γ or TNF-α [19,20] .…”
Section: Discussionmentioning
confidence: 99%